Developing Sustainability Literacy Through STEM Learning: A Review - M. Haidar Helmi; Elly Herliani (SEAMEO QITEP in Science, 2021)
The future of human life is not only full of potential and development but also of challenges. Global challenges that will be faced start from the environmental crisis, poverty and social problems. The UN has formulated bold goals through 17 targets in the Sustainable Development Goals to deal with this sustainability problem. The education sector is a milestone in achieving these goals. Through education, sustainability can be achieved among other things by integrating design thinking into STEM learning which can promote sustainability literacy. This opportunity need to be follow up to develop Sustainability Model of Design Thinking as one innovation to enhance sustainability literacy.